THE RELATIONSHIP BETWEEN STRESS LEVEL AND SOCIAL ENVIRONMENT WITH SMOKING BEHAVIOR IN ADOLESCENTS AT SMPN 44 SURABAYA - Wahyuni, Intan Tri; Widayanti, Dini Mei; Mayasari, Ayu Citra (STIKES Cendekia Utama Kudus, 2024)
ABSTRACT Teenagers have a high enough curiosity because it makes teenagers try everything they have never experienced. During this period, adolescents experience changes both physically, psychologically, and socially. The age of smokers is getting younger because smokers believe that cigarettes have a calming function when they are anxious and stressed. The research objective was to analyze the relationship between stress levels and the social environment with smoking behavior in adolescents.The research design used a cross sectional method. Total population is 235 people and probability sampling technique with stratified random sampling approach. The variables of this study are the level of stress and the social environment with smoking behavior using a questionnaire that has been tested for validity and reliability. Data were analyzed with Spearman's rho test and chi square test.Spearman Rho statistical test results obtained a significance value of 0.003. The significance value is less than 0.005. This means that stress levels are related to smoking behavior in adolescents at SMPN 44 Surabaya. The Chi-Square statistical test results obtained a significance value of 0.000. The significance value is less than 0.005. This means that the social environment is related to smoking behavior in adolescents at SMPN 44 Surabaya.For adolescent smokers, it is hoped that they will change their smoking habits with more positive activities. For teenagers who do not smoke, it is hoped that they will stay away from cigarettes and invite people around them to reduce and even avoid smoking. Keywords: Smoking behavior, social environment, stress level and adolescents.